ANALISIS HUBUNGAN PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS ATAS BELANJA MODAL PADA PEMERINTAH DAERAH KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH - Oktora, Fahri Eka; Pontoh, Winston (ACCOUNTABILITY, 2013)
Local governments need to increase capital investment in fixed assets, such as: equipments, buildings, infrastructures, and other fixed assets. Capital expenditure allocation was based on the local needs for facilities and infrastructure. The higher level of capital investment expected to improve the quality of public services, because the fixed assets due to capital expenditure is a key for the implementation of governmental duties and provides services to the public. This study was aimed at analyzing the corelations of local own revenues, general allocation funds, and specific allocation funds with capital expenditures at Tolitoli Regency in Central Sulawesi Province. Research design methods is the field research by correlation analysis. Test results showed a lack relationship between local own revenues with capital expenditures by R value was 0,155. Meanwhile the relationship between general allocation funds with capital expenditures was 0,981 and special allocation funds with capital expenditures was 0,427. It shows the close relationship between the two variables with capital expenditures.